RATIONAL NUTRITION OF ATHLETES AS THE BASIS OF A HEALTHY LIFESTYLE AND MAINTENANCE OF AN APPROPRIATE LEVEL OF PHYSICAL ACTIVITY - Гончар, Галина; Затуливітер, Анастасія (SWorldJournal, 2023)
One of the most important biosocial categories integrating ideas about a certain type of human activity is a way of life. It is characterized by the features of a person's daily life, which include his work, daily life, ways of using free time, satisfacti